The Repetitive Mechanical Tactile Stimulus Intervention Effects Depend on Input Methods - Watanabe, Hiraku; Kojima, Sho; Otsuru, Naofumi; Onishi, Hideaki (Frontiers in Neuroscience, 2020)
Elderly and stroke patients often have low spatial two-point discrimination function. The intervention effect of repetitive mechanical tactile stimulation has been shown to improve the spatial two-point discrimination function. The methods of tactile input are classified as either Active Touch or Passive Touch. In Passive Touch, the tactile stimulus is passively applied on the skin without voluntary movement, whereas in Active Touch, it is applied with voluntary movement. Based on the method of tactile input, tactile stimulation activate different cerebral cortex areas. A previous study reported that the tactile stimulation with Active Touch activate posterior parietal cortex, activated during a spatial two-point discrimination task. Therefore, the present study aimed to investigate the effects of two mechanical tactile stimulation intervention methods on two-point discrimination: tactile stimulation with voluntary movement (Active Touch) and without voluntary movement (Passive Touch). We recruited 15 healthy volunteers aged 20–23 years and applied tactile stimuli on their right index finger for 10 min. The mechanical tactile stimulator comprised 24 tiny plastic pins driven by piezoelectric actuators. In the Active Touch intervention, the pin was rubbed by voluntary movement of the right index finger (abduction 0°–10°) after the appearance of 12 pins. The Passive Touch intervention stimulated the index finger with the 12 pins setting at the centre of index finger. Tactile thresholds were measured using a two-point discrimination measurement device. Two-point discrimination threshold showed significant reduction after Active Touch intervention compared with those pre-intervention. Two-point discrimination threshold were not significantly modulated after Passive Touch intervention; however, significant negative correlation was observed between the intervention effect on two-point discrimination threshold and the performance pre-intervention. This study suggesting that the effects of repetitive mechanical tactile stimulation depend on the method of tactile input. An effective intervention for improving two-point discrimination threshold is the application of Active Touch condition for 10 min.